Association Between Ambient Air Pollutants Exposure and Preterm Birth in Women Who Underwent in vitro Fertilization: A Retrospective Cohort Study From Hangzhou, China - Shi, Wenming; Jiang, Meiyan; Kan, Lena; Zhang, Tiantian; Yu, Qiong; Wu, Zexuan; Xue, Shuya; Fei, Xiaoyang; Jin, Changbo (Frontiers in Medicine, 2021)
Objectives: Exposure to air pollutants has been linked to preterm birth (PTB) after natural conception. However, few studies have explored the effects of air pollution on PTB in patients who underwent in vitro fertilization (IVF). We aimed to investigate the association between ambient air pollutants exposure and PTB risk in IVF patients. Methods: This retrospective cohort study included 2195 infertile women who underwent IVF treatment from January 2017 and September 2020 in Hangzhou Women’s Hospital. Totally 1005 subjects who underwent a first fresh embryo(s) transfer cycle were analyzed in this study. Residential exposure to ambient six air pollutants (PM2.5, PM10, SO2, NO2, CO, O3) during various periods of the IVF timeline were estimated by satellite remote-sensing and ground measurement. Cox proportional hazards models for discrete time were used to explore the association between pollutants exposure and incident PTB, with adjustment for confounders. Stratified analyses were employed to explore the effect modifiers. Results: The clinical pregnancy and PTB rates were 61.2% and 9.3%, respectively. We found that PM2.5 exposure was significantly associated with an increased risk of PTB during 85 days before oocyte retrieval [period A, adjusted hazard ratio, HR=1.09, 95%CI: 1.02-1.21], gonadotropin start to oocyte retrieval [period B, 1.07 (1.01-1.19)], first trimester of pregnancy [period F, 1.06 (1.01-1.14)], and the entire IVF pregnancy [period I, 1.07 (1.01-1.14)], respectively. An interquartile range increment in PM10 during periods A and B was significantly associated with PTB at 1.15 (1.04-1.36), 1.12 (1.03-1.28), and 1.14 (1.01-1.32) for NO2 during period A. The stratified analysis showed that the associations were stronger for women aged < 35 years and those who underwent two embryos transferred. Conclusions: Our study suggests ambient PM2.5, PM10 and NO2 exposure were significantly associated with elevated PTB risk in IVF patients, especially at early stages of IVF cycle and during pregnancy.